The December 2018 eruption at Etna volcano: a geochemical study on melt and fluid inclusions - Correale, Alessandra; Corsaro, Rosa Anna; Miraglia, Lucia; Paonita, Antonio; Rotolo, Silvio G. (Frontiers in Earth Science, 2024)
This study presents new data on major and trace element geochemistry of olivine-hosted melt inclusions (MI) in volcanic products from the Mt Etna December 2018 eruption, with the aim of investigating the geochemical characteristics of the feeding magma. The noble gas geochemistry of fluid inclusions (FI) in olivines was also investigated. Major element composition of MIs is variable from tephrites/trachybasalt to phonotephrite/basaltic trachyandesite, with SiO2=45.51-52.72 wt%, MgO=4.01-6.02 wt%, and CaO/Al2O3=0.34-0.72. Trace element patterns of MIs present a typical enrichment in LILE and LREE, depletion in HFSE and relatively fractionated REE patterns: (La/Lu)N= 18.8 -41.08, with Eu/Eu*=(0.5 -1.8). Positive anomalies in Sr (Sr/Sr*= 0.8 -2.3) and Ba can be ascribed to the assimilation of plagioclase-rich cumulates in the magmatic reservoir. The variable Ba/La (9.8 -15.8), K/Nb (260 -1037), Ce/Nb (1.9-3.4), Rb/La (0.4-1.6) and Ba/Nb (10.8-25.8) ratios reveal mixing between two end-member magmas comparable to those emitted from i) the 2001 Upper Vents and 2002-03 Northern Fissures (Type-1) and ii) the 2001 Lower Vents and 2002-03 Southern fissures (Type-2), respectively. Type-2 represents a magma that underwent the influence of a crustal component, whereas Type-1 is compatible with an HIMU-MORB type heterogeneous mantle source. It appears that the 2018 MI have captured the two different magmas and the lack of homogenization may imply a very fast ascent (a few months). Compatible with the contemporary presence of primordial HIMU-MORB and crust-contaminated endmembers, are the data of noble gases from FI that highlighted an 3 He/ 4 He of 6.5-6.6Ra. The hypothesis of two different magmas identified by the trace elements geochemistry in MI is thus reinforced by helium isotopic data in FI -2018 eruption together to data from etnean other eruptions -and allows inferring a bicomponent magma mixing.